Tratamento de resíduos sólidos da indústria têxtil - Ramos, Fabrícia Maribondo da Silva (2009)
Due to the progressive technological development, a number of industries in the world are growing and consequently the quantity of sludge and industrial waste generated, making it a common problem in many parts of Brazil and the world. Therefore, it is important the development of an alternative and more effective process to replace the simple disposal of these wastes in industrial landfills. Thus, this study aimed to evaluate the incorporation of textile waste in clay matrices for the production of ceramic blocks with no structural function through the solidification / stabilization (S/S) process. Initially, the textile waste and clay characterization, used as matrices for the production of the ceramic blocks, was carried out. The chemical composition of textile waste varies, and contains Al, Fe, Mn, Na,Pb, Cu, Zn and Cr, from the textile process and the treatment of sewage generated in the process. The waste was classified as a not dangerous and not inert residue, according to NBR 10004/2004 of the Associação Brasileira de Normas Técnicas (ABNT). Based upon published studies, preliminary tests were performed with addition of 10% of textile waste in ceramic blocks to evaluate the method of burning and its influence on the mechanical strength and water absorption of ceramic blocks. It was decided to continue the research, working with slow process of drying and burning process of the blocks in industrial kiln for ceramic blocks (for 72 hours, with temperatures ranging from 850 to 1000 º C).Subsequently, blocks with compositions of 5, 10, 15, 20 and 25% of textile waste were prepared. The mixture was made proportionately with a percentage of dry mass. For comparative analysis of the chemical characteristics of these blocks incorporated with textile waste, ceramic blocks only with clay were produced. Experimental results indicated that concentrations of analyzed metals in both leached and solubilized extracts from ceramic blocks with incorporation of textile waste were below the limits set by the NBR 10004/2004 ABNT - Solid Residue. Thus they can be classified as non-hazardous and inert, offering no risk of future contamination of soil during their lifetime, as well as when disposed in landfill after their use. Experimental results related to the brick compressive strength showed that all the proportions of incorporation met the requirements of NBR 15270-3/2005 from ABNT. Results also showed that, with up to 20% of textile waste added to the bricks, water absorption met the requirements of NBR 15270-3/2005 from ABNT. The proportion of 15% of incorporation of textile sludge in the ceramic body, was considered one that guarantees the best technical conditions of production, this way, a statistical evaluation of the possible occurrence of metals volatilization during burning process was carried out, and with a reliability set at 95%, it was possible to observe that there was no metal volatilizing during the ceramic blocks firing stage. That way, it can be observed that the S / S process was able to effectively immobilize the metals present in the textile waste into the ceramic blocks.